High SARS-CoV-2 tropism and activation of immune cells in the testes of non-vaccinated deceased COVID-19 patients - Guilherme M. J. Costa; Samyra M. S. N. Lacerda; André F. A. Figueiredo; Natália T. Wnuk; Marcos R. G. Brener; Lídia M. Andrade; Gabriel H. Campolina-Silva; Andrea Kauffmann-Zeh; Lucila G. G. Pacifico; Alice F. Versiani; Maísa M. Antunes; Fernanda R. Souza; et al. (BMC Biology, 2023)
Abstract Background Cellular entry of SARS-CoV-2 has been shown to rely on angiotensin-converting enzyme 2 (ACE2) receptors, whose expression in the testis is among the highest in the body. Additionally, the risk of mortality seems higher among male COVID-19 patients, and though much has been published since the first cases of COVID-19, there remain unanswered questions regarding SARS-CoV-2 impact on testes and potential consequences for reproductive health. We investigated testicular alterations in non-vaccinated deceased COVID-19-patients, the precise location of the virus, its replicative activity, and the immune, vascular, and molecular fluctuations involved in the pathogenesis. Results We found that SARS-CoV-2 testicular tropism is higher than previously thought and that reliable viral detection in the testis requires sensitive nanosensors or RT-qPCR using a specific methodology. Through an in vitro experiment exposing VERO cells to testicular macerates, we observed viral content in all samples, and the subgenomic RNA’s presence reinforced the replicative activity of SARS-CoV-2 in testes of the severe COVID-19 patients. The cellular structures and viral particles, observed by transmission electron microscopy, indicated that macrophages and spermatogonial cells are the main SARS-CoV-2 lodging sites, where new virions form inside the endoplasmic reticulum Golgi intermediate complex. Moreover, we showed infiltrative infected monocytes migrating into the testicular parenchyma. SARS-CoV-2 maintains its replicative and infective abilities long after the patient’s infection. Further, we demonstrated high levels of angiotensin II and activated immune cells in the testes of deceased patients. The infected testes show thickening of the tunica propria, germ cell apoptosis, Sertoli cell barrier loss, evident hemorrhage, angiogenesis, Leydig cell inhibition, inflammation, and fibrosis. Conclusions Our findings indicate that high angiotensin II levels and activation of mast cells and macrophages may be critical for testicular pathogenesis. Importantly, our findings suggest that patients who become critically ill may exhibit severe alterations and harbor the active virus in the testes.